Revealing the Relevance of Activity Based Costing Accounting in Single Product Manufacturing: Evidence from Coffee Processing MSMEs in Indonesia - Muhammad Sapril Sardi Juardi; Yogi Hady Afrizal; Jamaluddin Majid; Hardiwansyah (Academic Bright Collaboration, 2026)
Purpose –This study seeks to enhance the accuracy of Activity‑Based Costing (ABC) relative to traditional methods in determining the Cost of Goods Sold for a single product coffee enterprise. The research gap emerges because prior studies predominantly examine industries with complex product lines, while the application of ABC in single product MSMEs remains understudied, leaving its theoretical contribution insufficiently explored.Methods –This study employs a qualitative case study at CV Berkat Asia, a single product coffee MSME. Data analysis integrates interviews with the production manager to identify activities and cost drivers, supported by annual production cost reports. The ABC method is applied through a two-stage allocation process across four cost pools.Findings – The results showed that the traditional method caused an undercosting of IDR 2.09 per unit, or an aggregate total of IDR 2,608,835 over ten months of production. This distortion arises from the use of a single volume-based overhead rate that does not reflect resource consumption at the batch and facility level, such as machine fuel and quality inspection. In contrast, the ABC method provides a more accurate cost allocation by tracing overhead to the activities actually consumed.Research implications –This study challenges the prevailing assumption that ABC is applicable only to complex industries and demonstrates its relevance for single product MSMEs by enhancing cost transparency and supporting more robust strategic decision making. In doing so, the study offers a meaningful theoretical contribution to cost accounting literature within the context of small and simple manufacturing entities.